Local Radiotherapy Affects Drug Pharmacokinetics—Exploration of a Neglected but Significant Uncertainty of Cancer Therapy. (December 2017) - Chen, Yu-Jen; Tsai, Tung-Hu; Wang, Li-Ying; Hsieh, Chen-Hsi
Purpose: Concurrent chemoradiation therapy is the mainstay of treatment for many types of malignancies. However, concurrent chemoradiation therapy is associated with a greater number of systemic adverse effects than radiotherapy or chemotherapy alone. Summary: Pharmacokinetics is the study of a drug and/or its metabolite kinetics in the body, including absorption, distribution, metabolism, and elimination. The incidences of adverse effects are markedly higher in patients who receive concurrent chemoradiation therapy than in those who receive either radiotherapy or chemotherapy alone. This phenomenon implies that irradiation affects the pharmacokinetics of cytotoxic agents, namely the radiotherapy–pharmacokinetic phenomenon. Experimental animal studies have shown that local irradiation affects the systemic pharmacokinetics of 5-fluorouracil and cisplatin at both low dose (simulating generous dose distributed to normal tissues) and daily practice dose (mimicking therapeutic dose to target volumes). These effects are significant in the circulation of blood and lymphatic system as well as in the hepatobiliary excretion. Furthermore, recent studies have demonstrated that matrix metalloproteinase-8 plays an important role in the radiotherapy–pharmacokinetic phenomenon. Conclusion: In the present review, we provide a general overview of the radiotherapy–pharmacokinetic phenomenon and discuss the possible mechanisms governing the phenomenon.